(untitled) (Scientific journal of the Fergana State University, 2024)
The article discusses the prospects for using the capabilities of modern virtual reality in the information society system, the introduction of virtual reality into the education system, the strategic meaning of the socio-philosophical assessment of the indicators of the manifestation of virtual reality. The article discusses the directions of research into virtuality, the influence of virtual reality on humanity, the organization and regulation of human life, and analyzes the significance of comparison. As well as improving skills in the effective use of modern information and communication technologies among young people, the use of virtual reality in the field of science, the transformation of social institutions in the context of the development of the information society, the development of Internet associations and their cooperation with traditional associations, the development and influence of the Internet on changing the system of social communications, as well as the transformation of modern education.